2020
DOI: 10.1088/1361-6528/ab83b4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ni substitution on structural, magnetic and electronic properties of epitaxial CoCr2O4 spinel thin films

Abstract: Cubic spinel CoCr 2 O 4 has attained recent attention due to its multiferroic properties. However, the Co site substitution effect on the structural and magnetic properties has rarely been studied in thin film form. In this work, the structural and magnetic properties of Co 1x Ni x Cr 2 O 4 (x = 0, 0.5) epitaxial thin films deposited on MgAl 2 O 4 (100) and MgO (100) substrates to manipulate the nature of strain in the films using pulsed laser deposition (PLD) technique are presented. The epitaxial nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Its normalised Co 2p core level was therefore subtracted from that of the other two samples to give the different spectras “CSCF3‐CSCF1” and “CSCF2‐CSCF1” displayed in the bottom part of Figure 4b as blue and red open circles, respectively. Their line shape was fitted with two spin‐orbit doublets, ascribed to Co 2+ and Co 3+ oxidation states, for the main peaks and one for the high BE satellite [70, 71]. The overall fit is found to superimpose well with the experimental data and confirms the difference in the line shape between the two spectra.…”
Section: Resultssupporting
confidence: 56%
“…Its normalised Co 2p core level was therefore subtracted from that of the other two samples to give the different spectras “CSCF3‐CSCF1” and “CSCF2‐CSCF1” displayed in the bottom part of Figure 4b as blue and red open circles, respectively. Their line shape was fitted with two spin‐orbit doublets, ascribed to Co 2+ and Co 3+ oxidation states, for the main peaks and one for the high BE satellite [70, 71]. The overall fit is found to superimpose well with the experimental data and confirms the difference in the line shape between the two spectra.…”
Section: Resultssupporting
confidence: 56%
“…32 The O 1s spectrum can be divided into three groups of peaks centred at 529.72 eV, 531.44 eV, and 532.82 eV, which are ascribed to the characteristic peaks of lattice oxygen (O latt ), adsorbed oxygen (O ads ), and free H 2 O, respectively. 33 Particularly, it has been widely reported that the peak at 531.5 eV indicates the presence of a large number of oxygen vacancies in the CoCr 2 O 4 samples, 34,35 which are greatly favourable for enhancing the surface adsorption capacity of the catalysts as well as improving their light absorption properties. After the compositing of CoCr 2 O 4 and g-C 3 N 4 , the binding energies of C and N elements are shifted slightly to the lower energy region, while the binding energies of Co and Cr elements are shifted to the higher energy region.…”
Section: Resultsmentioning
confidence: 99%
“…It has been generally recognized that the characteristic peak at 531.4 eV signifies the possible existence of oxygen vacancy defects in the structure of ZnCr 2 O 4 . The presence of abundant oxygen vacancies will form a defective energy level that is able to greatly improve the photocatalytic performance of ZnCr 2 O 4 . , It is worth noting that the relative intensity values of the O ads peak to the O latt peak in the ZCO-ZIS-0.6 composite sample are substantially higher than those in the ZnCr 2 O 4 sample, suggesting that the relative concentration of oxygen vacancies in the composite increases sharply, which should be related to the employment of the strongly reducing glycerol in the compositing experiment. To further verify the existence of oxygen vacancy defects in the ZnCr 2 O 4 sample as well as in the ZCO-ZIS-0.6 composite, electron paramagnetic resonance (EPR) tests are performed, and the results are supplied in Figure f.…”
Section: Resultsmentioning
confidence: 99%